Multiple impacts of the COVID-19 pandemic and antimicrobial stewardship on antimicrobial resistance in nosocomial infections: an interrupted time series analysis - Li, Weibin; Yang, Xinyi; Liu, Chaojie; Liu, Xu; Shi, Lin; Zeng, Yingchao; Xia, Haohai; Li, Jia; Zhao, Manzhi; Yang, Shifang; Li, Xiaojie; Hu, Bo; et al. (Frontiers in Public Health, 2024)
The emergency response to the COVID-19 pandemic may disrupt hospital management activities of antimicrobial resistance (AMR). This study aimed to determine the changing AMR trend over the period in China when stringent COVID-19 response measures were implemented.Methods: This retrospective study was conducted in a designated hospital for COVID-19 patients in Guangzhou, China from April 2018 to September 2021. The prevalence of 13 antimicrobial-resistant bacteria was compared before and after the COVID-19 responses through Chi-square tests. Interrupted time series (ITS) models on the weekly prevalence of AMR were established to determine the changing trend. Controlled ITS models were performed to compare the differences between subgroups.Results: A total of 10134 isolates over 1265 days were collected. And antimicrobial-resistant strains presented in 38.6% of the testing isolates. The weekly AMR prevalence decreased by 0.29 percentage point (95% CI [0.05-0.80]) after antimicrobial stewardship (AMS) policy, despite an increase in the prevalence of penicillin-resistant Streptococcus pneumoniae (from 0/43 to 15/43, p<0.001), carbapenem-resistant Escherichia coli (from 20/1254 to 41/1184, p=0.005), and carbapenem-resistant Klebsiella pneumoniae (from 93/889 to 114/828, p=0.042). And the changing trend did not vary by gender (male vs female), age (<65 vs ≥65 years), service setting (outpatient vs inpatient), care unit (ICU vs non-ICU), the primary site of infection (Lung vs others), and Gram type of bacteria (positive vs negative).The response to COVID-19 did not lead to an increase in overall AMR; however, it appears that management strategy on the prudent use of antimicrobials likely contributed to a sizable long-term drop. The frequency of several multidrug-resistant bacteria continues to increase after the COVID-19 epidemic.